Philippine directory of foundations - Lim, Narzalina Z. (The SCC Development and Research Foundation, 1974)
The product of the first attempt to compile a Philippine Directory of Foundations, the directory includes 131 foundations. Information on each foundation includes: address, date of establishment, date of NSDB certification(if NSDB-certified foundation), objectives and purposes, modes of activity, field of interest, financial data in regard to net assets and income, and information on the internal organization of the foundations.